Addition of glucose to a fatty meal delays chylomicrons and suppresses VLDL in healthy subjects - Westphal, S.; Leodolter, A.; Kahl, S.; Dierkes, J.; Malfertheiner, P.; Luley, C. (European journal of clinical investigation, 2002)
Background Postprandial lipemia has been shown in a number of studies to be associated with atherosclerosis. However, the test meals used in these studies were heterogeneous particularly in their carbohydrate content, which may be important for the resulting lipemia and which makes comparison between different studies difficult. We studied the effect of 75 g glucose added to a fatty meal on various lipoproteins and on gastric emptying. Materials and methods Fourteen healthy young volunteers were studied in the fasting state and until 7 h postprandially. In a crossover design, each subject received an oral fat load (1 g fat kg−1 body weight) with or without 75 g glucose. Triacylglycerol (TG) and free fatty acids (FFA) were then measured in whole blood and lipoproteins were separated off by ultracentrifuging. Gastric emptying was determined by the 13C breath test. Results The addition of 75 g glucose to a fatty meal had two different effects. Gastric emptying was delayed by about 2 h and the chylomicron response was consequently postponed. In addition, the postprandial increase in VLDL triacylglycerol was reduced by 40%, which may be due to the pronounced FFA depression during the glucose‐induced rise in insulin. Conclusions 75 g glucose added to an oral fat load causes a delay of the chylomicron response and a marked suppression of the postprandial increase in VLDL.